Ruptured Ovarian Pregnancy: Unusual Presentation of Unusual Diagnosis- A Case Report - Sushruti Kaushal; Sunil Thakur; Saurabh Sharma; Shyam Bhandari (Asian Journal of Medical Research, 2018)
High index of suspicion is essential for the diagnosis of ectopic pregnancy and should be considered in any female of reproductive age presenting with acute abdomen.